Financial risk management: Approach to optimise the internal control systems at Fraport AG - Schneider, Katja (2006)
Summary In order to use chances a company must be willing to assume risks. Against the background of shareholder and stakeholder aspects, markets getting more volatile as well as the use of chances in an environment geared to competition, the conscious analysis of taking risks gets more and more important. Risk management means deliberately dealing with taking risks. Suitable processes have to be implemented on all company levels in order to deal with risks. The so-called financial risks resulting from fluctuations of exchange rates and interest rates, which was traditionally and predominantly regarded as a risk concerning banks and other financial service providers, have increased considerably for industrial companies. A distinct and working financial risk management and the pertaining internal control system are indispensable and form an essential part of the overall managment. In the dissertation "Financial risk management: Approach to optimise the internal control systems at Fraport AG" the hypothesis that the financial risk management of Fraport AG can be optimised is investigated by analysing theory and practice. The actual situation at Fraport is presented, the demand for optimisation is shown and recommendations for actions are educed in order to improve the situation. The main emphasis is placed on the internal control systems, i.e. the design of the management of the risks itself (e. g. hedging) is not in the focus of consideration. The basis of the consideration are the legal outline conditions and the operational necessity of an optimised conceptual design of the financial risk management with special emphasis being placed on the design of the internal control systems. The work presents the processes proposed in theory as well as their implementation in practice. The information about the practical implementation is gathered by means of interviews with experts of different companies.